Sheltering from the storm: The role of a quality improvement collaborative focused on improving HIV care retention in New Orleans during and following Hurricane Ida - Emily A. Arnold; Shannon Fuller; Bruce D. Agins; Lauren Fidelak; Jessica Xavier; Wayne T. Steward; Greg M. Rebchook; Kimberly A. Koester (PLoS ONE, 2025)
Background Climate-related events, including hurricanes in New Orleans, Louisiana (NOLA), are becoming more intense and frequent, presenting challenges to HIV-related health care system facilities, staff, and patients. Addressing these challenges through quality improvement collaboratives (QICs) may blunt their impact through redesign of systems, leading to improved retention in HIV care during severe disruptions. We present a case study of a federally-supported QIC that was in progress to improve care engagement when Hurricane Ida struck in August 2021. Methods We conducted key informant interviews with providers, health department staff, and capacity building specialists involved in the QIC. These interviews were augmented by fieldnotes from 4 learning sessions, day-long workshops that featured clinic-level and jurisdiction-level presentations and brainstorming, including efforts to improve emergency preparedness and respond to hurricanes. Results Immediate disruptions included damage and loss of physical buildings, homes, electrical power, and displacement of clients and providers/staff. These disruptions contributed to significant barriers to accessing HIV care and treatment. Efforts to overcome barriers resulted in solutions to help clients gain access to HIV treatment, especially at pharmacies in nearby states, to which they were evacuated or voluntarily relocated. Being part of the QIC and using QIC-related listservs and messaging apps allowed HIV-care teams to more effectively connect with clients, facilitate access to treatment, and feel less isolated as they navigated the hurricane’s impact. Although the QIC was not originally focused on climate change or disaster relief, following the hurricane, the necessity of addressing emergency preparedness became clear to ensure continuity of care during climate-related events. Conclusions There is an urgent need to build health care system resiliency against climate-related disasters and emergencies. QICs offer a vehicle for strengthening systems and assuring quality of care to address disasters and prepare for them, crises that are unfortunately ever more frequent as climate change advances.